Abundance, distribution and species composition of cyclopoid copepods along a transect traversing the upwelling zone off Northern Zamboanga Peninsula, Philippines. - Jaspe, Beverly Tudence (2018.)
Cyclopoids are small-sized zooplankton and prey of sardines. It is thus important to study their abundance, species composition and distribution in an area which is considered to be the largest sardine fishing ground in the Philippines. This study was conducted to provide insight on the relationship between oceanographic processes like upwelling and zooplankton production and predation. Zooplankton samples were collected in six stations along a transect extending from the coast to about 50km offshore in Dipolog Bay on the northeast coast of Zamboanga Peninsula in Mindanao during the Northeast monsoon. A 100 μm NorPac net was hauled vertically to sample successive depth strata (0-65 m, 65-135 m, 135-200 m). Cyclopoids were the second most abundant taxa (12.2%) out of 28 major groups of zooplankton, with an overall mean density of 503.6 ind./m^3. Forty two (42) cyclopoid species were identified from Dipolog bay with Oncaea clevei (25.4%) being the highest, followed by Oncaea scottodicarloi (13.6%), Triconi conifera (9.2%), Oncaea media (7.2%) and Corycaeus dahlia (7.0%), respectively. Omnivorous Oithona species were most abundant and diverse in upwelling stations whereas carnivorous Corycaeus were high in abundance and diversity in the non-upwelling zone. The high abundance of cyclopoids in the uppermost layer (732.9 ind./m^3) at 0-65 m and low abundance (220.2 ind./m^3) in the deepest stratum at 135-200 m is attributed to the abundance of phytoplankton in upper euphotic zone where there is high intensity of light. The cyclopoid density was lowest at Station 2 (237.3 ind./m^3) and highest in Station 4 (938.3 ind./m^3), the margin of upwelling zone. The increase in cyclopoid density as a response to phytoplankton build-up in upwelling zone can be seen on the margin because of the drift that disperses them.
Thesis (Graduate, Master in Biology) College of Arts and Sciences, Graduate Program, University of the Philippines Visayas, 2018..
Keywords: Cyclopoid Copepods -- Northern Zamboanga Peninsula -- philippines